Bank profitability in times of quantitative easing: The role of Central Bank transparency - Athanasios Koukouridis (Economies, 2025)
To stabilize economies, central banks implemented unconventional monetary policies like quantitative easing following the global financial crisis. Although much research has been done on how quantitative easing affects financial markets, the influence of central bank transparency on bank profitability under such policies is still underexplored. This paper looks at how central bank transparency affects bank profitability in advanced countries under unconventional monetary policy. Using a panel dataset of commercial banks from 25 advanced economies (2013-2019), we apply a two-step Generalized Method of Moments (GMM) estimator to handle any endogeneity. Focusing on central bank transparency as a main transmission route, the model accounts for macroeconomic factors and bank-specific characteristics. The results show that central bank transparency greatly improves bank profitability together with quantitative easing. Although other elements, macroeconomic conditions and bank-specific characteristics, support transparency as a vital channel via which monetary policy influences the operation of the banking sector. This paper provides recommendations for legislators trying to enhance the effectiveness of unconventional policies in various institutional contexts by highlighting the need for central bank transparency as a channel for monetary policy efficacy.
Keywords: E51; E52; E58; G21; 330; bank profitability; monetary policy; quantitative easing; central bank transparency; panel data